Changes in out‐of‐pocket charges associated with obstetric care provided under Medicare in Australia. (12th January 2018) - Callander, Emily; Fox, Haylee
Abstract : Recent health reforms alongside unregulated provider fees have led to increased attention being given to out‐of‐pocket healthcare costs. This study utilised annual statistics published by the Department of Health for services provided under the Medicare Benefits Schedule (MBS) from 1992/3 to 2016/17 to identify changes in out‐of‐pocket charges for obstetric items over time, and estimate the change in demand for obstetric items in response to price increases. Since 1992/3 out‐of‐pocket charges increased by 1035% for out‐of‐hospital items and 77% for in‐hospital items. Demand for obstetric items has reduced with increasing charges.